Motion database of disguised and non-disguised team handball penalty throws by novice and expert performers - Helm, Fabian (Data Brief, 2017)
This article describes the motion database for a large sample (n = 2400) of 7-m penalty throws in team handball that includes 1600 disguised throws. Throws were performed by both novice (n = 5) and expert (n = 5) penalty takers. The article reports the methods and materials used to capture the motion data. The database itself is accessible for download via JLU Web Server and provides all raw files in a three-dimensional motion data format (.c3d). Additional information is given on the marker placement of the penalty taker, goalkeeper, and ball together with details on the skill level and/or playing history of the expert group. The database was first used by Helm et al. (2017) [1] to investigate the kinematic patterns of disguised movements. Results of this analysis are reported and discussed in their article “Kinematic patterns underlying disguised movements: Spatial and temporal dissimilarity compared to genuine movement patterns” (doi:10.1016/j.humov.2017.05.010) [1].